Tinjauan Azitromisin Pada Penyakit Virus Korona 2019 (COVID-19) - Donsu, Yosefien Christania; Hasmono, Didik (Universitas Muhammadiyah Surakarta, 2020)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV-2. The World Health Organization has declared this disease a pandemic, where the scale of the spread of the disease occurs globally throughout the world. Currently, there is no validated pharmacological treatment for COVID-19 disease, and is still in the clinical trial stage. Azithromycin in conjunction with hydroxychloroquine or chloroquine has been proposed as a treatment that can improve the prognosis of COVID-19. This review aims to describe the mechanism of action and effectiveness of azithromycin in the treatment of COVID-19 patients. The review of the article literature was carried out through internet searches by accessing the database from google scholar, PubMed, and science direct sites. The inclusion criteria in this review are articles using azithromycin in clinical trials and COVID-19 therapy which were published from December 2019 to October 2020. Azithromycin is a macrolide antibacterial and is based on studies having antiviral and immunomodulatory effects. The use of azithromycin can lower viral load when added to hydroxychloroquine in COVID-19 patients based on small-scale clinical studies. Azithromycin used with hydroxychloroquine or chloroquine has shown good results, although it raises concerns about the risk of increased side effects of prolonged QT interval so that monitoring of the heart is needed and proven in a larger number of COVID-19 patients. The decision to use azithromycin must take into account the potential benefits and risks, evaluating the possibility of the drug being more effective than the risks to the patient.